2010
DOI: 10.1007/s11274-010-0603-4
|View full text |Cite
|
Sign up to set email alerts
|

Inductive effect produced by a mixture of carbon source in the production of gibberellic acid by Gibberella fujikuroi

Abstract: Gibberellic acid has been known since 1954 but its effect on rice still remains very important in the agricultural world. Gibberellic acid (GA3) is the main secondary metabolite produced by the Gibberella fujikuroi fungus. This hormone is of great importance in agriculture and the brewing industry, due to its fast and strong effects at low concentrations (μg) on the processes of growth stimulation, flowering, stem elongation, and germination of seeds, among others. Plant promoters of growth production such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…It was observed that GA production initiated on the first day of fermentation, which is contrary to reports that GA commences about 46 h after the initiation of fermentation following nitrogen depletion in the medium (Escamilla et al, 2000;Rodrigues et al, 2009;Rios-Iribe et al, 2011). However, Lale and Gadre (2010) also reported GA production at 20 h by a mutant of G. fujikuroi.…”
Section: Resultscontrasting
confidence: 72%
“…It was observed that GA production initiated on the first day of fermentation, which is contrary to reports that GA commences about 46 h after the initiation of fermentation following nitrogen depletion in the medium (Escamilla et al, 2000;Rodrigues et al, 2009;Rios-Iribe et al, 2011). However, Lale and Gadre (2010) also reported GA production at 20 h by a mutant of G. fujikuroi.…”
Section: Resultscontrasting
confidence: 72%
“…Meanwhile, the root lengths of three osipms1 mutants were significantly increased by amino acids treatment compared to those in untreated seeds (Figure b–e). Ketogenic amino acid, for example Leu, Ile, and Phe, can be degraded directly into acetyl‐CoA for GA biosynthesis (Rios‐Iribe et al ., ). Here, we predicted that amino acid treatment contributing to seed vigour of osipms1 mutants might be through stimulating GA biosynthesis during seed germination.…”
Section: Resultsmentioning
confidence: 97%
“…There are reports that the production of phytohormones, like that of several other secondary metabolites, is initiated by the exhaustion of nitrogen (Shukla (Fox & Howlett 2008;Rios-Iribe et al 2011) sources from the medium (Brückner 1992;Tudzynski 1999). Maximal IAA, GA and ethylene production by F. culmorum strains was observed in 96-h cultures, when the sources of carbon and nitrogen in the culture (results not shown) were largely depleted.…”
Section: Discussionmentioning
confidence: 90%